Activities of Trovafloxacin and Ampicillin-Sulbactam Alone or in Combination versus Three Strains of Vancomycin- Intermediate Staphylococcus aureus in an In Vitro Pharmacodynamic Infection Model - Aeschlimann, Jeffrey R. (American Society for Microbiology, 2000)
The recent isolation of clinical strains of methicillin-resistant Staphylococcus aureus (MRSA) with intermediate susceptibility (MICs, 8 μg/ml) to vancomycin (vancomycin-intermediate S. aureus [VISA]) emphasizes the importance of developing novel antimicrobial regimens and/or agents for future treatment. We studied the activities of ampicillin-sulbactam and trovafloxacin alone or in combination against three unique strains of VISA in an in vitro infection model. Two VISA strains were trovafloxacin susceptible (MICs, ≤2 μg/ml); one VISA strain was trovafloxacin resistant (MIC, 4 μg/ml). Trovafloxacin was administered to simulate a dose of 200 or 400 mg every 24 h. Ampicillin-sulbactam was administered to simulate a dose of 3 g every 6 h. Samples were removed from the infection models over 48 h, and reductions in colony counts were compared between regimens. Trovafloxacin (200 mg) produced rapid killing of a control MRSA strain over the 48-h experiment but produced only slight killing of all three VISA strains. The higher dose of trovafloxacin improved killing but did not produce bactericidal activity at 48 h. Ampicillin-sulbactam produced rapid bactericidal activity against all four strains tested, and colony counts at 8 h were at the limits of detection. However, regrowth occurred by 48 h for each strain. The combination of ampicillin-sulbactam and trovafloxacin provided additive activity against two of the three VISA strains. In conclusion, trovafloxacin or ampicillin-sulbactam alone did not provide adequate activity against the VISA strains for the 48-h evaluation period, but the combination could help improve activity against some strains of VISA.